MODERN TECHNOLOGY DEVICES IN EFL TEACHING - LESTARI, YUNDA
This paper aims at making a review of positive experiences that used modern technology devices in classrooms of English as a foreign language around the world. Some modern technology devices will be reviewed, they are: Tablet PCs, smartphone and iPads. For this review, four articles by researchers from different countries were selected in order to obtain positive reports on the use of modern technology devices in EFL classroom. Despite modern technology devices are still rare and not being popular in some areas in Indonesia, the use of that kinds of device as a learning tool is being largerly developed in Indonesia and other countries and it has shown good results so far.